THE ASSOSIATION BETWEEN THE LEVEL OF KNOWLEDGE, ATTITUDES, AND AVAILABILITY OF FACILITIES WITH THE PRACTICE OF NURSES AND CLEANING SERVICES HOSPITALIZATION UNIT IN MEDICAL WASTE MANAGEMENT X KUDUS HOSPITAL - Risma Dwi Yulianti; Yusniar Hanani Darundiati; Hanan Lanang Dangiran (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
The activities in hospital produce many kinds of medical waste. If medical waste is not managed well, it can cause a bad impact for health and environmental. Good knowledge, attitudes and practices for nurses and cleaning services as well as adequate facilities are required in the management of hospital medical waste. Hospitalization is the unit that contributes the most medical waste compared other units. The purpose of this research is to know the assosiation of knowledge level, attitude and availability of facility with practice of nurses and cleaning services hospitalization unit in medical waste management RS X Kudus. This research is a quantitative research with cross-sectional approach. The population in this study is 52 nurses and 12 cleaning services in RS X Kudus. The sample in this study consisted of 35 nurses counted using Slovin formula and cleaning services as much as 12 people. Data collection using questionnaires. Data analysis using Chi-Square test. The results showed that the knowledge and attitude variable of the nurses was related to the nurse's practice of knowledge (p-value = 0,022) and attitude (p-value = 0,004). While the variables of knowledge related to cleaning service practice (p-value = 0,001). Variable attitude is not related to cleaning services practice (p-value = 0,081), availability of facilities is not related to nursing and cleaning service practice. The conclusion of this research is there is correlation between knowledge, attitude nurses and knowledge cleaning services with practice of nurses and cleaning services in medical waste management RS X Kudus.